Nanosecond Time‐Resolution Study of Gold Nanorod Rotation at the Liquid–Solid Interface. Issue 14 (20th April 2016) - Neupane, Bhanu; Chen, Fang; Wei, Yanli; Fang, Ning; Ligler, Frances S.; Wang, Gufeng
Abstract: Early studies showed that the adsorption of nanorods may start from a special "anchored" state, in which the nanorods lose translational motion but retain rotational freedom. Insight into how the anchored nanorods rotate should provide additional dimensions for understanding particle–surface interactions. Based on conventional time‐resolution studies, gold nanorods are thought to continuously rotate following initial interactions with negatively charged glass surfaces. However, this nanosecond time‐resolution study reveals that the apparent continuous rotation actually consists of numerous fast, intermittent rotations or transitions between a small number of weakly immobilized states, with the particle resting in the immobilized states most of the time. The actual rotation from one immobilized state to the other happens on a 1 ms timescale, that is, approximately 50 times slower than in the bulk solution. Abstract : In a spin : A nanosecond time‐resolution study yields new insights into the rotational motion of anchored rod‐like nanoparticles at the liquid–solid interface. The continuous rotation observed under low temporal resolution is found to be comprised of numerous fast, intermittent transitions between a limited number of weakly immobilized states.